Perbaikan Kualitas Kerja Dengan Desain Alat Penopang Kepala Bagi Buruh Suwun Di Pasar Badung Denpasar - I Made Bulda Mahayana (Poltekkes Kemenkes Denpasar, 2021)
Abstract : One side of industrialization have followed the progress of science and technology in the formal workers, informal workers the other hand very little attention from the government, such as suwun workers lift transport of goods in the Market Badung, Denpasar. The purpose of research is to identify the workload and subjective complaints suwun workers before and after using the tool supporting head in the Market Badung, Denpasar. This type of research is pre experiment with the same study design subject of a pattern of